Assessing waste separation behaviour in Nigeria: implications for post-Covid-19 pandemic waste management strategies - Osotuyi, T.B.; Zhao, S.; Abioye, O.; Mgbachi, U.P.; Falebita, O.A. (IOP Publishing, 2025)
During medical emergencies, effective management of waste is crucial to preventing the spread of infections, protecting healthcare workers, and ensuring the safety of the broader society. The recent COVID-19 pandemic has underscored the importance of waste separation for efficient waste management and public health protection. However, Nigeria's situation has not been addressed by research investigation despite its potential to shape waste management policy implementation and citizen alignment. Therefore, the current study examines the waste separation behaviour of Nigerian residents during the pandemic, utilizing an extended Theory of Planned Behaviour framework. The authors achieve this by analyzing survey data from 726 residents in two highly populated cities (Lagos and Oyo states). All the latent variables in the theory of planned behaviour show a positive and significant effect on waste separation behaviour, with attitudes emerging as the strongest influence. Past behaviour positively correlates with the intention to separate waste. However, the results of perceived policy effectiveness indicate a significantly negative moderating effect on the relationship between intention and waste separation behaviour. This outcome suggests a continuous need for public enlightenment with greater focus on policy implementation and enforcement in Nigeria. Infrastructure for waste separation should receive more attention, as the absence of suitable waste segregation bins or disposal facilities weaken environmental policy implementation and Nigerians cultivation of waste separation behaviour. This study provides policy direction to enhance waste separation practices for day-to-day environmental safety and preparedness in the event of future health emergencies.